The Philosophy of Early Christianity - Karamanōlēs, Giōrgos E. (Ancient Philosophies Ser, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication Page -- Contents -- Preface to the second edition, 2021 -- Preface to the first edition, 2013 -- Abbreviations -- Introduction -- 1 The Christian conception of philosophy and Christian philosophical methodology -- 2 Physics and metaphysics: first principles and the question of cosmogony -- 3 Logic and epistemology -- 4 Free will and divine providence -- 5 Psychology: the soul and its relation to the body -- 6 Ethics and politics -- 7 Conclusion -- Appendix: the protagonists -- Further reading -- Bibliography -- Index.